PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSI DI KECAMATAN CISARUA BOGOR TAHUN 2021-2022 - Gina Mahira (2022)
This study aims to discuss the role of the United Nations High Commissioner for Refugees (UNHCR) as an international organization that specializes in dealing with refugees, in Cisarua Subdistrict, Bogor in 2021-2022. This study uses role theory by Clive Archer which classifies the role of international organizations as instruments, arenas, and independent actors. The method used in this research is descriptive qualitative method by taking data sources from primary data and secondary data. The data collection technique is done by interview and documentation process. In this study, the authors analyze data by collecting various data, then selecting and filtering the data which will then be linked to the existing theory, after that a temporary hypothesis will appear which will later become the answer to the research question. The result of this research is the role of UNHCR in dealing with refugees in Cisarua Subdistrict based on the theory of the role of international organizations by Clive Archer is the role as an instrument. This role can be seen from the UNHCR whose main objective is to provide protection and assistance and asylum status to refugees in this case can be carried out. Refugees in Cisarua Subdistrict already have official refugee status registered in UNHCR through an identity card, although not all of them are registered. Then the refugees there also receive basic life supports from UNHCR and their partner although it is limited. Keywords : UNHCR, role, refugee, Cisarua Subdistrict, The Middle East